2020
DOI: 10.1101/2020.07.31.230698
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Muscle Metabolic Energy Costs While Modifying Propulsive Force Generation During Walking

Abstract: We pose that an age-related increase in the metabolic cost of walking arises in part from a redistribution of joint power where muscles spanning the hip compensate for insufficient ankle push-off and smaller peak propulsive forces (FP). Young adults elicit a similar redistribution when walking with smaller FP via biofeedback. We used targeted FP biofeedback and musculoskeletal models to estimate the metabolic costs of operating lower limb muscles in young adults walking across a range of FP. Our simulations su… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…This redistribution could explain, at least in part, why elderly people pay greater metabolic energy costs for walking than younger people and might therefore be considered maladaptive 50 . The functional consequences of higher metabolic energy costs include reduced physical activity and independence, gait ine ciency, and lower quality of life 51 . In our study, the experimental group showed signi cant improvements in muscle strength of the trunk and lower extremities after EX1 exercise.…”
Section: Discussionmentioning
confidence: 99%
“…This redistribution could explain, at least in part, why elderly people pay greater metabolic energy costs for walking than younger people and might therefore be considered maladaptive 50 . The functional consequences of higher metabolic energy costs include reduced physical activity and independence, gait ine ciency, and lower quality of life 51 . In our study, the experimental group showed signi cant improvements in muscle strength of the trunk and lower extremities after EX1 exercise.…”
Section: Discussionmentioning
confidence: 99%